Non-Ideal Cyclic Voltammetry of Redox Monolayers on Silicon Electrodes: Peak Splitting is Caused by Heterogeneous Photocurrents and Not by Molecular Disorder - Zhang, S.; Lyu, X.; Hurtado Torres, C.; Darwish, Nadim; Ciampi, Simone (AMER CHEMICAL SOC, 2022)
Over the last three decades, research on redox-active monolayers has consolidated their importance as advanced functional material. For widespread monolayer systems, such as alkanethiols on gold, non-ideal multiple peaks in cyclic voltammetry are generally taken as indication of heterogeneous intermolecular interactions-namely, disorder in the monolayer. Our findings show that, contrary to metals, peak multiplicity of silicon photoelectrodes is not diagnostic of heterogeneous intermolecular microenvironments but is more likely caused by photocurrent being heterogeneous across the monolayer. This work is an important step toward understanding the cause of electrochemical non-idealities in semiconductor electrodes so that these can be prevented and the redox behavior of molecular monolayers, as photocatalytic systems, can be optimized.